TRANSFORMASI KEPEMIMPINAN BIROKRASI - Anwaruddin, Awang (Jurnal Borneo Administrator, 2006)
Since the last five decades, the behaviourist have scientifically analyzed the implementation of leadership within organizations, and found that leadership is a complicated process that can be described in various theories and models. However, there are a lot of contradictive and over-lapped hypotheses and types of leadership. Hence, it’s difficult to define the ideal leadership. The difficulty is due to the misunderstanding of leadership concept, started from the idea that leadership is something that you own or gain-the same as a certain position in the structure of organization. However, if you have the desire and willpower, no matter who you are and where you work, you can become an effective leader through a never ending process of self-study, education, training, and experience. To inspire your workers into higher levels of teamwork, for example, there are certain things you must learn, understand, and do. These do not come naturally, but are acquired through continual work and study. Good leaders are continually working and studying to improve their leadership skills; they are not resting on their laurels.  Keywords: transformasi kepemimpinan, birokrasi.